The odd quantum - Treiman, Sam B. (Princeton, N.J. : Princeton University Press, 1999)
"This is a concise but comprehensive account of quantum mechanics written by a respected physicist for popular science readers. Sam Treiman makes quantum mechanics accessible to nonspecialists, combining mastery of the material with clear, elegant prose and infectious enthusiasm as he conveys the substance, methods, and profound oddities of the field."--Jacket
Newton's law, gravity, energy, electromagnetism, special relativity -- Electromagnetic waves, blackbody radiation, early spectroscopy, the Rutherford atom, Bohr's quantum model, De Broglie's matter waves -- The two-slit experiment Schroedinger's wave equation, probabilistic interpretation, a brief survey of the rules, communting observables, the uncertainty principle, momentum, the operator concept, angular momentum, aspects of energy -- The free particle, particle in a box, the harmonic oscillator, central potentials generally, the one-electron atom, the infinite solenoid, decay processes -- Symmetry, antisymmetry rules, the Pauli principle, the Fermi gas, atoms, more on identical Bosons -- Particles in collistion, particles in decay, accelerators, patterns and regularities, basic ingredients, summary -- Free fields, free particles, interactions, Feynman diagrams, virtual particles, the standard model in diagrams.
Includes bibliographical references (pages 255-256) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Quantum theory; Quantum Theory; Théorie quantique; SCIENCE -- Physics -- Quantum Theory; SCIENCE -- Physics -- General; Quantum theory; Quantenmechanik; Quantisierung; Kwantummechanica; Théorie quantique; QUANTUM THEORY; THEORETICAL PHYSICS; FIELD THEORY (PHYSICS); Quantum theory; Andre fag (naturvidenskab og teknik) -- Andre fag